2013
DOI: 10.1016/j.jsat.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and availability of onsite non-rapid and rapid HIV testing in US substance use disorder treatment programs

Abstract: Racial and ethnic minorities and injection drug users (IDUs) are at increased risk of HIV infection. To date, the associations between these caseload characteristics and availability of onsite HIV testing in substance use disorder treatment programs are unknown. This uses data collected in 2008–2009 from 198 program administrators of treatment programs participating in the National Institute on Drug Abuse’s Clinical Trials Network to address this gap in the literature. Results show positive associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Studies examining treatment programs affiliated with the Clinical Trials Network (CTN) indicate that a little over 48% of programs provide on-site testing (Abraham et al, 2013; Brown et al, 2006; Strauss, Des Jarlais, Astone, & Vassilev, 2003). Research on HIV services has also been reported using data from the National Drug Abuse Treatment System Survey (NDATSS).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining treatment programs affiliated with the Clinical Trials Network (CTN) indicate that a little over 48% of programs provide on-site testing (Abraham et al, 2013; Brown et al, 2006; Strauss, Des Jarlais, Astone, & Vassilev, 2003). Research on HIV services has also been reported using data from the National Drug Abuse Treatment System Survey (NDATSS).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant differences found in the present study in receipt of HIV test results may be attributed to the fact that the study design addressed major barriers to testing found in prior research including lack of funding and training (Abraham et al, 2012; Bini et al, 2011; Brown et al, 2006; 2007; Knudsen & Oser, 2008). Nevertheless, these findings of cross modality effectiveness of on-site testing, are very encouraging in light of the differences in implementation of HIV testing across modalities found in prior survey research (Brown et al, 2007; Polinksy et al, 1998; Pollack & D’Aunno, 2010).…”
Section: Discussionmentioning
confidence: 54%
“…Staff training in HIV testing for counselors and program administrators of drug treatment programs should be made widely available. Such training could be delivered through the State or Local Health Departments’ AIDS Administrations, through local medical schools, or through the regional Center for Substance Abuse Treatment’s Addiction Technology and Transfer Centers (Abraham et al, 2012). Funding is also needed to support testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations